Conduction disorders after perimembranous ventricular septal defect closure: continuous versus interrupted suturing techniques. (22nd September 2021) - Yoneyama, Fumiya; Kato, Hideyuki; Matsubara, Muneaki; Mathis, Bryan J; Yoshimura, Yukihiro; Abe, Masakazu; Suetsugu, Fuminaga; Maruo, Kazushi; Suzuki, Yasuyuki; Hiramatsu, Yuji
Abstract: OBJECTIVES: The aim of this study was to investigate postoperative conduction disorder differences between continuous and interrupted suturing techniques for the closure of perimembranous outlet-type ventricular septal defects (VSDs) in both tetralogy of Fallot (ToF) and isolated VSD cases. METHODS: Patients aged 4 years or younger who underwent VSD closure for ToF ( n = 112) or isolated perimembranous outlet-type VSD ( n = 73) from April 2010 to December 2018 at 3 centres were reviewed. Patients either received continuous suturing for ToF (C-ToF, n = 58) or isolated VSD (C-VSD, n = 50), or interrupted suturing for ToF (I-ToF, n = 54) or isolated VSD (I-VSD, n = 23). Cohorts did not differ in preoperative characteristics. Postoperative conduction disorder differences upon discharge and postoperative year 1 (POY1) were evaluated by electrocardiography. RESULTS: The C-ToF group showed significantly shorter PQ intervals (124.0 vs 133.5 ms; P = 0.042 upon discharge, 125.3 vs 133.5 ms; P = 0.045 at POY1) and QRS durations (98.0 vs 106.2 ms; P = 0.031 upon discharge, 97.3 vs 102.5 ms; P = 0.040 at POY1) than the I-ToF group. Right bundle branch block incidence was significantly lower in the C-ToF versus I-ToF groups (56.8 vs 75.9; P = 0.045 upon discharge, 56.8 vs 75.9; P = 0.045 at POY1). Heart rates were significantly lower in the C-ToF versus I-ToF groups at POY1 (109.2 vs 119.3 bpm; P < 0.001). No parameters significantly differed between C-VSD and I-VSD groups. Multivariable analyses confirmed the group (C-ToF versus I-ToF) as a significant covariate in postoperative heart rate, PQ interval, QRS duration and right bundle branch block outcomes at POY1 ( P = 0.013, 0.027, 0.013 and 0.014, respectively). CONCLUSIONS: A continuous suturing technique for the closure of outlet-type VSD in ToF could reduce the incidence of postoperative right bundle branch block, shorten the PQ interval and lower heart rate. Subject collection: 110, 138, 139. Abstract : Postoperative conduction disorders in ventricular septal defect (VSD) closure are well-recognized complications of both isolated VSD and tetralogy of Fallot (ToF) repair.